OP0023 ACPA-POSITIVE RHEUMATOID ARTHRITIS PATIENTS BENEFITED MORE FROM ADVANCED TREATMENT STRATEGIES THAN ACPA-NEGATIVE RHEUMATOID ARTHRITISPATIENTS: 25-YEAR RESULTS OF A LONGITUDINAL COHORT STUDY. (June 2019) - Matthijssen, Xanthe; Niemantsverdriet, Ellis; Huizinga, Thomas; van der Helm - van Mil, Annette
Abstract : Background: Over the last 25 years, treatment of rheumatoid arthritis (RA) has changed considerably, and clinically relevant joint damage and deformations have become infrequent. It is unclear to what extent the long-term outcomes mortality, sustained drug-free remission (DFR) and physical functioning have improved, and whether ACPA+ and ACPA- patients have benefited equally from treatment-improvements. Objectives: To investigate the influence of treatment strategies that have been improved for 25-years on mortality, DFR and functionality, and whether these effects differed for ACPA+ and ACPA- RA-patients. Methods: In the Leiden early arthritis cohort, 1291 patients with RA (1987 criteria) were included between 1993-2016. Patients were treated in routine care; initial and subsequent treatment changed over time; divided in 5 inclusion periods. Patients included between 1993-1996 (n=168) received initial NSAIDs and started DMARDs with delay, patients included 1997-2000 (n=185) were treated early with mild DMARDs (e.g. hydroxychloroquine, penicillamine), in 2001-2005 (n=210) patients started early with methotrexate, in 2006-2010 (n=338) early methotrexate was followed by treat to target treatment adjustments; in 2011-2016 (n=390) this was similar and additional efforts were undertaken for very early referral. Patients were followed yearly including assessments of swollen joints, DAS28-ESR and health assessment questionnaires (HAQ). Mortality data were obtained from the civic registry. DFR was defined as the persistent absence of synovitis after cessation of DMARD-therapy during all available follow-up (≥ 1 year). DAS28-ESR and HAQ data were analysed with linear mixed models; mortality and time to DFR with multivariable and univariable Cox regression. Inclusion period 1993-1996 was used as reference. Analyses were stratified for ACPA-status (anti-CCP2). Results: Baseline age, sex and antibody status did not differ between inclusion periods. With 1993-1996 as reference, the DAS28-ESR decreased in the first year and thereafter remained lower in all inclusion periods (all p<0.05). Compared to 1993-1996, mortality was decreased in all inclusion periods (1997-2000 HR 0.67 (0.46;0.99); 2001-2005 HR 0.66 (0.45;0.97); 2006-2010 HR 0.64 (0.42;0.98); 2011-2016 HR 0.31 (0.14;0.68)). DFR achievement was faster in 2006-2010 (HR 2.68 (1.68;4.29)) and 2011-2016 (3.37 (1.97, 5.74)), compared to 1993-1996. Additionally, HAQ over time was lower in 2006-2010 (-0.25 (-0.36;-0.14)) and 2011-2016 (-0.21 (-0.32;-0.10)). Stratification for ACPA revealed that ACPA+ patients in the first two inclusion periods remained to have a higher DAS28-ESR over time (1993-1996 β 0.76 (0.42;1.10); 1997-2000 β 0.40 (0.07;0.74)); thereafter there was no difference in DAS28-ESR between ACPA+ and ACPA- patients. The decrease in mortality was similar for ACPA+ and ACPA- patients. The increased rate of DFR was more prominent in ACPA+ patients than ACPA- patients in the two most recent inclusion periods (2006-2010 HR ACPA+: 3.85 (1.25;11.9); ACPA- 2.27 (1.34;3.83); 2011-2016 HR ACPA+: 6.48 (1.89;22.2); ACPA-: 3.04 (1.66;5.55)). Within ACPA+ RA, the HAQ over time had improved in 2001-2005 (-0.19 (-0.34;-0.04)), 2006-2010 (-0.35 (-0.49;-0.22)) and 2011-2016 (-0.26 (-0.40;-0.13)), compared to 1993-1996. This effect was absent ACPA- RA. Conclusion: Improvements in treatment strategies during the last 25 years have resulted in lower disease activity, less mortality, more DFR and better physical functioning of RA-patients. ACPA+ patients, traditionally the most severe subset, benefited most from these improvements and have become more similar to ACPA- patients. Disclosure of Interests: Xanthe Matthijssen: None declared, Ellis Niemantsverdriet: None declared, Thomas Huizinga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, GSK, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience Inc., Nycomed, Boeringher, Takeda, Zydus, Epirus, Eli Lilly, Annette van der Helm - van Mil Grant/research support from: The research leading to these results has received funding from the European Research Council (ERC) under the European Union's Horizon 2020 research and innovation programme (Starting grant, agreement No 714312) and from the Dutch Arthritis Foundation. The funding source had no role in the design and conduct of the study.